Biosimilar Insulins: Basic Considerations. (January 2014) - Heinemann, Lutz; Hompesch, Marcus
Until now most of the insulin used in developed countries has been manufactured and distributed by a small number of multinational companies. Beyond the established insulin manufacturers, a number of new players have developed insulin manufacturing capacities based on modern biotechnological methods. Because the patents for many of the approved insulin formulations have expired or are going to expire soon, these not yet established companies are increasingly interested in seeking market approval for their insulin products as biosimilar insulins (BI) in highly regulated markets like the EU and the United States. Differences in the manufacturing process (none of the insulin manufacturing procedures are 100% identical) can lead to insulins that to some extent may differ from the originator insulin. The key questions are if subtle differences in the structure of the insulins, purity, and so on are clinically relevant and may result in different biological effects. The aim of this article is to introduce and discuss basic aspects that may be of relevance with regard to BI.